Empirical Testing of Real Profit Management, Good Coorporate and Firm Value in the Financial Services Sector in Indonesia - Mamay Komarudin (Journal of Research in Business, Economics, and Education, 2021)
The purpose of this research is 1) to analyze the effect of real profit on the value of the company; 2) to analyze the influence of managerial ownership on firm value; 3) to analyze institutional ownership as a moderation variable in the effect of real profit on firm value ; 3) to analyze managerial ownership as a moderation variable in the effect of real profit on firm value. This research is based on exoplanet research. The population is all financial sector service companies as many as 77 companies. Based on the sample criteria, it was selected into 25 companies. Data analysis method using Moderating Regression Analysis. Based on the results of data analysis shows the following conclusions.1) real profit management to the firm value; 2) institutional ownership has a significant effect on the firm value; 3) managerial ownership has no significant effect on the firm value; 4) Significant institutional ownership moderates in the effect of real profit on the firm value. 5) Managerial ownership does not significantly moderate in the effect of real profit on the firm value.